Nomadics against parasites: subversive practices in the contemporary city - Mateo-Cecilia, Carolina; Finichiu, Alice; Braschi, Cristina (Arte, Individuo y Sociedad, 2018)
The way in which art and architecture have reacted to the social and material reality in the recent modern history has been varied. If artistic practices under utopian-idealistic approaches priorized utopian practices as a reaction to the expansive urbanism of a post-war Europe, at the turn of the 20th Century, and especially after 2008, our concerns are others. The attempt to rebalance the imbalances caused by urbanization processes that took place the first decade of the 20th Century has questioned the mercantilization of the existing city, this time with actions linked to reality, developed with a pragmatic attitude. Discussing Fiuza Faustino 2007 work “Illegality” which stated, “The illegality as the only liberated territory within the Metropolis” (2008), in this article we identify everyday actions, attitudes of resistance expressing their rejection to a hierarchical organization of pre-crisis architectural scenarios and exhibiting the urgency of renovation. These artistic and architectural practices work with the possibilities of subversive practices, as devices that accommodate new distributions of power. Such ephemeral and itinerant attitudes are exemplified in temporary appropriations that re-describe the existing city, which are no longer escaping from the reality, given the lifetime that we are living.
Keywords: Architectural devices; parasites; nomadism; urban resistance; dissidence; pragmatic architecture